hypoerbolic identities

• Jul 7th 2012, 08:32 PM
Magical
hypoerbolic identities
starting from the definition of sinhx, show that when x is real the real value of sinh^-1x is given by sin^-1(x)=ln((x+root(x^2+1))
• Jul 7th 2012, 08:53 PM
Prove It
Re: hypoerbolic identities
Quote:

Originally Posted by Magical
starting from the definition of sinhx, show that when x is real the real value of sinh^-1x is given by sin^-1(x)=ln((x+root(x^2+1))

\displaystyle \displaystyle \begin{align*} y &= \sinh^{-1}{x} \\ \sinh{y} &= x \\ \frac{e^y - e^{-y}}{2} &= x \\ e^y - e^{-y} &= 2x \\ e^{2y} - 1 &= 2x\,e^y \\ e^{2y} - 2x\,e^y &= 1 \\ e^{2y} - 2x\,e^y + \left(-x\right)^2 &= \left(-x\right)^2 + 1 \\ \left( e^y - x \right)^2 &= x^2 + 1 \\ e^y - x &= \pm \sqrt{x^2 + 1} \\ e^y &= x \pm \sqrt{x^2 + 1} \\ y &= \ln{\left( x \pm \sqrt{x^2 + 1} \right)} \end{align*}

But of course, this is only defined for positive values of \displaystyle \displaystyle \begin{align*} x \pm \sqrt{x^2 + 1} \end{align*}, and since \displaystyle \displaystyle \begin{align*} \sqrt{x^2 + 1} > x \end{align*} for all real \displaystyle \displaystyle \begin{align*} x \end{align*}, that means

\displaystyle \displaystyle \begin{align*} \sinh^{-1}{x} \equiv \ln{\left( x + \sqrt{x^2 + 1} \right)} \end{align*}